Women Farmer in Patriarchal Power: Eco-feminism Study in Subak Bulung Daya Antap Village Tabanan Regency Bali - Ni Made Wiasti; I Nyoman Suarsana (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Despite the Balinese people having strong eco-feminism based on their religious beliefs, five patriarchal powers have marginalized their role in the traditional rice-field system, known as subak. This paper seeks to demonstrate the existence of women farmers within patriarchal power with an ecofeminism approach in Subak Bulung Daya, Antap Village, Tabanan Regency. Qualitative methods with critical ethnographic analysis were implemented. According to this study, women are responsible for carrying out agricultural rituals and helping their husbands in all agricultural activities. However, patriarchal power marginalizes women in the subak system and must accept a double burden in the domestic and public spheres, thus demonstrating a paradoxical model of eco-feminism. This study found that even in patriarchal oppression, Balinese women still play an important role in maintaining ecological balance through various rituals as local wisdom.